Manajemen Krisis PT. Kereta Api Indonesia (Persero) Di Masa Pandemi COVID-19 - Anggara, Ari Panca (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to determine how crisis management is carried out by the Public Relations Unit (USP) of PT. Kereta Api Indonesia (Persero) during the COVID-19 pandemic. This research was conducted using a descriptive method with a qualitative approach, using primary and secondary data sources, and the data collection techniques used were observation, in-depth interviews, and documentation. The results obtained are the Public Relations Unit (USP) of PT. Kereta Api Indonesia (Persero) performs crisis management, namely by; 1) Crisis Identification: observation and data collection and data analysis; 2) Crisis Isolation: Preparing HR and Coordination with all units; 3) Post-Crisis Recovery: synergize with government programs, publications and promotions and evaluation of crisis control.